(3eLehY jTJed Ydi cJGH aj hUa GdNjd hCNHGQgG hQLGdgG hCeQGVgG hWQb YdGLgGs ((3Yaja GdOjf YHO Gddg Hf CMeO MHjQg s)
(3ChdgG (B:s
(3jHJOF CKfGA GdCMGOjK GdhGQOI ai GdNjd s
(3BNQgG (B:s
(3hbjd Ef YeQ Gdajd KdKeGFg SfI hbGdhG XgQ ajd ai CjGe GdeJhcd hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG WjHkG eHGQckG ajg Edi jhe GdbjGeI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdcjejGA h GdWHjYjGJs